2017
DOI: 10.1590/1980-5373-mr-2016-0943
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Lubricating Properties of Diesel Based Fuels Micro Emulsified With Glycerin

Abstract: The mineral diesel oil sold in Brazil, due to environmental reasons; presents sulfur concentration of 10 ppm, which causes a deficiency of lubricity, since sulfur is one of the chemical species that gives a good lubricating characteristic. Poor lubricity affects performance and causes failure of engine parts. This study aimed to evaluate the use of glycerin as an antiwear additive by means of tribological tests of the mineral diesel S10 B7 and 10 formulations of diesel based fuels, micro emulsified with 0% (di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…They highlighted that oxygen-carrying moieties enhance the lubricity and film strength of the additive. Additionally, Uchoa et al [54] observed that fatty compounds have better lubrication due to oxygen atoms, which provides polarity to the molecule and, consequently, adhesion to the metal surface; these oxygen-carrying moieties are present in the produced biodiesel.…”
Section: Discussionmentioning
confidence: 99%
“…They highlighted that oxygen-carrying moieties enhance the lubricity and film strength of the additive. Additionally, Uchoa et al [54] observed that fatty compounds have better lubrication due to oxygen atoms, which provides polarity to the molecule and, consequently, adhesion to the metal surface; these oxygen-carrying moieties are present in the produced biodiesel.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, glycerol has been applied as an additive in industrial processes or products with a large carbon footprint. For instance, E. Silva Santos et al used glycerol as an additive in emulsified marine diesel [291]. The authors reported an improvement of the lubricity and water reduction when a glycerol solution was added up to 15%.…”
Section: Strategies Of Glycerol Applicationmentioning
confidence: 99%
“…However, the desulphurization process of diesel fuel has a negative impact, namely decreasing the lubricity ability of the fuel, due to the loss of compounds that are essential for its lubricity ability, such as polyaromatic and polar compounds [5]. The low lubricity properties of diesel fuel can speed up the wear and tear on vehicle engines [6]. The solution that can be applied to overcome this problem is by adding a substance to diesel fuel, which can increase its lubricity ability [7].…”
Section: Introductionmentioning
confidence: 99%